Characterization of lead-free alkali niobate piezoceramics by the Inverse Method - Ogo, Kenji; Weiß, Manuel; Rupitsch, Stefan; Lerch, Reinhard; Kakimoto, Ken-Ichi (Ultrasonics Symposium (IUS), 2015 IEEE International, 2015)
Material constants of manganese-doped sodium potassium niobate (NKN) were characterized by the Inverse Method, which provides material constants by minimizing deviations between frequency-resolved electrical impedance measurements and finite element simulations. Impedance curves of two different types of ceramic samples featuring same geometric shape but different polarization directions, were measured in the temperature range of -25 degrees C to 150 degrees C. Material constants at each temperature were characterized by using the measured impedance curves. As a result, an anisotropic decrease of the elastic stiffness constants was observed with increasing temperature. It can be assumed that this temperature dependency is attributed to orthorhombic-tetragonal phase transition. Furthermore, the maximum loss factor was obtained at 75 degrees C, which caused minimum impedance range of all resonance-antiresonance pairs at the same temperature.
Keywords: lead-free; Inverse Method; piezoceramics